The digital teaching materials for craft subjects: The development to improve student learning outcomes - Nurhikmah, Nurhikmah; Hakim, Abdul; Saman, Abdul; Arfandi, Anas (Journal of Research in Instructional, 2025)
This study attempts to produce a digital product, especially teaching materials, and calculate its validity, practicality, and effectiveness. This study uses research and development. SMPN 3 Sungguminasa was the location of the study, which involved 28 students as research subjects. The study involved 1 craft subject teacher and 2 validators, who were content/material experts and media experts. We used various questionnaires for needs identification, validation by media experts, material experts, teachers and student responses, and learning outcome tests to collect data. The results of this study indicate that the identification of student needs meets the required qualifications. The digital book developed was declared very valid by media and material experts. The teacher and student response questionnaires declared the level of practicality to be very high. The pretest (40.71) and posttest (85.71) measured digital books, yielding a statistically significant value of 0.00. It can be concluded that the development of digital teaching materials for craft subjects is very much needed, valid, practical, and effective to improve student learning outcomes.